2017
DOI: 10.1021/acs.est.6b05843
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 40 Classes of Per- and Polyfluoroalkyl Substances in Historical Aqueous Film-Forming Foams (AFFFs) and AFFF-Impacted Groundwater

Abstract: Aqueous film-forming foams (AFFFs), containing per- and polyfluoroalkyl substances (PFASs), are released into the environment during response to fire-related emergencies. Repeated historical applications of AFFF at military sites were a result of fire-fighter training exercises and equipment testing. Recent data on AFFF-impacted groundwater indicates that ∼25% of the PFASs remain unidentified. In an attempt to close the mass balance, a systematic evaluation of 3M and fluorotelomer-based AFFFs, commercial produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
680
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 645 publications
(693 citation statements)
references
References 74 publications
13
680
0
Order By: Relevance
“…This information may be helpful in informing larger studies about information that should be collected to identify determinants of exposure. The higher concentrations of the PFHxS in this population compared to NHANES suggest that exposure could be increasing, and may be related to levels now being detected in water sources throughout the country (Hu et al, 2016; Barzen-Hanson et al, 2017). Further studies should investigate the relationships between PFAS levels in drinking water and serum levels, taking into account personal behaviors that may determine exposure (e.g.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This information may be helpful in informing larger studies about information that should be collected to identify determinants of exposure. The higher concentrations of the PFHxS in this population compared to NHANES suggest that exposure could be increasing, and may be related to levels now being detected in water sources throughout the country (Hu et al, 2016; Barzen-Hanson et al, 2017). Further studies should investigate the relationships between PFAS levels in drinking water and serum levels, taking into account personal behaviors that may determine exposure (e.g.…”
Section: Discussionmentioning
confidence: 79%
“…Given the longer half-life of PFHxS in serum, this may suggest past exposure to PFHxS in drinking water from sources that were recently contaminated. It is notable that many of the newly discovered PFASs in AFFF or AFFF-impacted drinking water could serve as precursors for PFHxS and/or PFHxA (Barzen-Hanson et al, 2017). For PFHxA, the high detection frequency of this PFAA compared to NHANES may be due to the fact that the laboratory where these samples were analyzed was recently established, resulting in very little blank contamination and low detection limits.…”
Section: Discussionmentioning
confidence: 99%
“…[6] PFASs have been used in the formulations of thousands of consumer goods [19] and are present in aqueous film-forming foam formulations used to suppress aviation fires in training scenarios. [20,21] As ar esult, they have contaminated surface and ground waters near thousands of airports and military installations. [22,23] In 2018, the Environmental Working Group reported that over 16 million people in the United States were exposed to drinking water with PFAS concentrations exceeding 10 ng L À1 .…”
mentioning
confidence: 99%
“…PFASs aid solvation of tetrafluoroethylene monomers and PTFE itself so that emulsion polymerization can occur. The second application is as surfactants in aqueous film-forming foams (AFFF) (Prevedouros et al 2006, Barzen-Hanson et al 2017, Wang et al 2017. AFFF are used to stop hydrocarbon fires, by coating the surface of the hydrocarbon with PFASs to prevent oxygen from reacting with the hydrocarbon.…”
Section: Structure and Functionmentioning
confidence: 99%
“…AFFF are used to stop hydrocarbon fires, by coating the surface of the hydrocarbon with PFASs to prevent oxygen from reacting with the hydrocarbon. AFFF have been extensively used by the military, especially in air craft hangers and air craft carriers, though they are also used in commercial airports (Barzen-Hanson et al 2017). The third application of PFASs is in various consumer products with water-, grease-, or stain-repellant properties (Prevedouros et al 2006, D'Hollander et al 2010, Schaider et al 2017.…”
Section: Structure and Functionmentioning
confidence: 99%